Shrinking budgets, improving care: Simplify processes and engage with patients. (16th March 2010) - Rich, Graham
Abstract : All countries are facing the question of how to maintain the quality of care in the face of static or shrinking health budgets. In the NHS it's estimated that savings of over £20bn need to be made in the next few years. Graham Rich and Phil Leonard (doi:10.1136/bmj.c1258 ) argue that the NHS can save money while maintaining and improving the quality of care and set out their views on how to do this. But Yair Zalmanovitch and Dana Vashdi (doi:10.1136/bmj.c1259 ) think that something will have to suffer